2019
DOI: 10.2147/ott.s198341
|View full text |Cite
|
Sign up to set email alerts
|

<p>ODC1 promotes proliferation and mobility via the AKT/GSK3β/β-catenin pathway and modulation of acidotic microenvironment in human hepatocellular carcinoma</p>

Abstract: Purpose: Ornithine decarboxylase 1 (ODC1)-an oncogene involved in the biosynthesis of polyamines-is commonly upregulated and associated with poor prognosis in numerous cancers. However, the role and mechanism of ODC1 in hepatocellular carcinoma (HCC) remains unclear. The aim of the present study was to investigate the role of ODC1 in HCC and clarify the latent molecular mechanisms. Material and methods: We used samples obtained from The Cancer Genome Atlas. The expression of ODC1 was also assessed in our addit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
17
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 23 publications
(17 citation statements)
references
References 29 publications
0
17
0
Order By: Relevance
“…Previous studies have shown that both ODC1 and PKM2 regulate the AKT/GSK-3β/β-catenin pathway and promote the development of various cancers. 18,22 Therefore, we determined whether DFMO and compound 3k exert synergistic effects on HCC cells via the AKT/GSK-3β/ β-catenin pathway. The Western blotting results showed that the combination treatment significantly decreased the expression of p-AKT (Ser473), p-GSK-3β (Ser9), and β-catenin in HepG2 and SMMC-7721 cells compared to single drugs and DMSO treatment ( Figure 7A, P<0.05).…”
Section: Odc1 Inhibitor Dfmo and Pkm2 Inhibitor Compound 3k Exert Synmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous studies have shown that both ODC1 and PKM2 regulate the AKT/GSK-3β/β-catenin pathway and promote the development of various cancers. 18,22 Therefore, we determined whether DFMO and compound 3k exert synergistic effects on HCC cells via the AKT/GSK-3β/ β-catenin pathway. The Western blotting results showed that the combination treatment significantly decreased the expression of p-AKT (Ser473), p-GSK-3β (Ser9), and β-catenin in HepG2 and SMMC-7721 cells compared to single drugs and DMSO treatment ( Figure 7A, P<0.05).…”
Section: Odc1 Inhibitor Dfmo and Pkm2 Inhibitor Compound 3k Exert Synmentioning
confidence: 99%
“…17 Our previous study showed that an acidic microenvironment (simulated by lactate) promoted proliferation and migration of HCC cells by increasing ODC1 expression. 18 In the current study, we aimed to reveal the relationship between the key lactate metabolism enzyme PKM2 and the polyamine metabolism enzyme ODC1, and to determine whether simultaneous inhibition of ODC1 and PKM2 by DFMO and compound 3k, respectively, exerts synergistic effects against HCC cells. The results suggested that this approach may represent a novel treatment for HCC.…”
Section: Introductionmentioning
confidence: 99%
“…Thus, prolactin signaling can end diapause via inhibition of FOXO3 as well as through synthesis of polyamines. In addition to other numerous roles, polyamines can also upregulate AKT1 [46,47], which in turn downregulates FOXO3 to allow proliferation. Hence, we propose that prolactin signaling can inhibit FOXO3 either directly or indirectly through polyamines in diapause species and signal the re-emergence of embryo from diapause by resuming cell growth and development.…”
Section: Promoter Analysismentioning
confidence: 99%
“…100% change of activity). It is noteworthy that ODC is a possible target in oncology, because it contributes to polyamine-induced cell proliferation and it is often overexpressed in breast, prostate, colorectal and endometrial cancers [19].…”
mentioning
confidence: 99%